PENGARUH PROFESIONALISME, KOMPETENSI, PERAN WHISTLEBLOWER DAN PENGALAMAN TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN PADA KEMENTERIAN KETENAGAKERJAAN RI - LUTHFIANA MEYDA KUSUMA; NURMALA AHMAR; JMV MULYADI (JURNAL ILMIAH MAKSITEK, 2021)
This research aims to analyze the influence of Professionalism, Competence, The Role of Whistleblowers, Experience on theAbility of Auditors in Detecting Fraud (Fraud). The study used a sample of internal auditors of the Inspectorate General of theMinistry of Manpower. The number of internal auditors sampled in this study amounted to 71 people, the data analysismethod used in this study is a descriptive statatistic analysis method, data quality test, classical assumption test andhypothesis test whose calculations are carried out using SPSS. Hypotheses in this study were tested using multipleregression analysis. The results showed that Professionalism, The Role of Whistleblowers, Experience had a significant andpositive effect on the Auditor's Ability to Detect Fraud. While competence has no effect on the ability of auditors in detectingfraud.